EFFECT OF ADDING DIFFERENT LEVELS OF TAMARIND PULP TO DRINKING WATER IN PRODUCTIVE PERFORMANCE FOR BROILER - & Ibrahim, Tarif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at the poultry farm Animal Production Department, College of Agriculture, University of Baghdad, Abu Ghraib, for the period from 19/9/2016 to 30/10 / 2016. (42 days) The object of this study was effect of adding different levels of tamarind pulp (0, 5, 15, 25 g / L ) to the drinking water on productive traits of broiler chicken. A total of 120 unsexed Ross 308, one day old, an initial weight 41.5 g was used in the experiment. Chicks were fed on starter diet for the first three weeks of age and finisher diet for the 4,5 and 6 weeks of age. Birds were distributed to four treatments, The first T0 control (without any addition), The second T5, third T15 and fourth T25 treatment added tamarind pulp in the drinking water in concentrations 5, 15 and 25 g / L drinking water respectively. The results indicated that the use tamarind pulp in drinking water in concentration 5 g / L water led to Significant improvement (P<0.05) in body weight, average body weight gain and Relative Growth Rate, while no significant differences was observed in Feed intake and feed conversion ratio, water intake rate, consumption of water to feed, the values of the Production Index, mortality rate between the control and concentrations treatments Significant improvement (P<0.05) in carcass weight, percentage weight to gizzard for male in T15 in comparison with the control, and The results showed significant improvement (P<0.05) in back cut weight for female in T5 in gizzard weight for male in T15. and The results showed significant decrease in liver weight for male in T5, percentage weight abdominal fat for both sex mix in T15, and not observed significant differences in heart weight for all treatments and both sex. Conclude from the study that the use of tamarind pulp at concentrate 5 g/ L in drinking water of broiler water leading to improvement productive performance birds of broiler.